Long-term patient-related quality of life after successfully treated aseptic non-unions of the long bones. Issue 7 (July 2021) - Walter, Nike; Kerschbaum, Maximilian; Pfeifer, Christian; Popp, Daniel; Freigang, Viola; Hinterberger, Thilo; Alt, Volker; Rupp, Markus
Highlights: Non-unions significantly reduce patient's quality of life. Consequences involve psychological symptom burden. Psychological screening and counseling should be implemented in clinical practice. Abstract: Background: Non-union after fracture depicts a devastating complication in trauma surgery and studies assessing patient-reported outcome measures after stable bone consolidation are rare. Therefore, we aimed to evaluate the long-term impact of aseptic long bone non-union on the patients' physical health state and psychological wellbeing. For this purpose, quality of life after successful surgical treatment of long bone non-union was assessed. Methods: Sixty-one patients with aseptic long bone non-union surgically treated in our department between November 2009 and March 2019 with achieved bone consolidation were included. Quality of life was evaluated with the EQ-5D and SF-36 outcome instruments as well as with an ICD-10 based symptom rating (ISR) and compared to normative data. Results: With a minimum follow-up time of one year after the last surgery (mean 4.7 ± 2.7 years) the mean physical health component score of the SF-36 was 38.9 ± 13.7 and the mean mental health component score of the SF-36 was 49.0 ± 5.9, indicating lower quality of life compared to German normative values of 48.4 ± 9.4 ( p  < .001) and 50.9 ± 8.8 ( p  = 1.61), respectively. The mean EQ-5D index value reached 0.827 ± 0.18 with an EQ-5D VAS rating of 64.4 ± 21.5 compared to scores of 0.922 ( p  < .001) and 72.9 ± 1.1 ( p  < .001) obtained from an age-matched reference population. Mean scores of the ISR did not reveal significant psychological symptom burden in any scale, while an individual analysis showed moderate to severe impairments in 11.5% of the patients in total. Conclusion: Even 4.7 years on average after surgically successful treatment of aseptic long bone non-union, patients still report significant lower quality of life in comparison to normative data. Future clinical studies on non-unions should focus on patient-related outcome measures. Newly emerging treatment strategies and interdisciplinary approaches should be implemented to improve the overall quality of life of non-union patients.